How Is Terrorism Changing Us? Threat Perception and Political Attitudes in the Age of Terror - Vergani, Matteo (Springer Singapore, 2018)
"This is an elegant and magisterial treatment of the matter of our times. The insights contained in this important book will be invaluable for psychologists and political scientists and for political analysts, practitioners and commentators. The book will also serve as a superb starting point for students and lay readers seeking a readable, but always scholarly, introduction of a psychological approach to political events. Not all journalists and politicians will welcome the author's policy recommendations but all of them need to read it." -Craig McGarty, Western Sydney University, Australia "This book provides compelling evidence on the ways in which terrorist violence undermines multicultural democracies in Australia, Europe, and the United States and rips at the very fabric of liberal democracy. Vergani arrives at this conclusion through the analysis of survey data and focused experiments informed intellectually by a rich blend of psychological, sociological, and political thinking." -Leonie Huddy, Stony Brook University, USA "Matteo Vergani's book provides a comparative analysis of a troubling phenomenon especially in established democracies and it is a valuable resource for grasping the complex array of causes underlying it. This is a smart and timely must read for those interested in the consequences of terrorism on political attitudes and opinion climates." -Gianpietro Mazzoleni, University of Milan, Italy How does the threat of terrorist violence undermine multicultural democracies? What are the psychological and social mechanisms that explain how the threat of terrorism can change political attitudes? What is the role of media in shaping the perception of terrorism threat? And what are the ethical responsibilities of journalists? This book presents analysis of survey data and experimental evidence collected in Australia, Europe and the United States, and discusses how terrorism erodes civil liberties, sows doubt about the loyalties of immigrants, and heightens the left-right ideological divide. Matteo Vergani is a postdoctoral researcher at Deakin University. His research focuses on political violence, its causes, its impact on society, and the study of what might prevent it.